1999
DOI: 10.1088/0967-3334/20/3/305
|View full text |Cite
|
Sign up to set email alerts
|

Latex vessels with customized compliance for use in arterial flow models

Abstract: The physical characteristics of the arterial wall exert a major influence over blood flow patterns and the pulse wave velocity is strongly affected by the elasticity of the vessel. We have developed a technique for manufacturing latex tubing which has physical characteristics similar to those of human arteries. Tubes were produced by painting a plastic rod of diameter 7 x 10(-3) m (the internal diameter of the superficial femoral artery) with liquid latex. The number of coats applied controlled the thickness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Thus, the linear relation between flow and pressure drop as observed in this study might not completely represent the in-vivo situation. Earlier studies have modeled the compliance vessel using fluid structure interaction formulation [1] and investigated in experiments the elastic material property [15]. Future in vivo studies using patient-specific artery models that incorporate the compliance characteristic of the artery wall and more complex lesion morphology might provide further insights.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the linear relation between flow and pressure drop as observed in this study might not completely represent the in-vivo situation. Earlier studies have modeled the compliance vessel using fluid structure interaction formulation [1] and investigated in experiments the elastic material property [15]. Future in vivo studies using patient-specific artery models that incorporate the compliance characteristic of the artery wall and more complex lesion morphology might provide further insights.…”
Section: Discussionmentioning
confidence: 99%
“…Because of these parameters creating materials with a similar stress-strain response to aortic tissue may not lead to models that behave similar to the vessel itself. Because of this, the compliance (or stiffness) of arteries has become the attribute which researchers attempt to mimic [10,16]. The manufacturing methods for creating both idealised and realistic AAA models have been previously reported [10,1621].…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, the compliance (or stiffness) of arteries has become the attribute which researchers attempt to mimic [10,16]. The manufacturing methods for creating both idealised and realistic AAA models have been previously reported [10,1621]. O’ Brien et al [19] and Doyle et al [20] have verified a lost wax manufacturing technique and reported that the variation in wall thickness for large vessel models manufactured using this technique was between 4–11%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, models have been used in a wide range of applications to verify the mathematical theories of blood flow and the response to various haemodynamic situations [1 ± 3]. Walker et al [4] reported that measurement on latex tubings simulating the femoral artery showed good agreement with the mathematical predictions of pulse wave velocity and also with similar static characteristics to human arteries. We have developed a low-cost, fast and easy technique for manufacturing latex tubings with thin-walled aneurysms which have physical characteristics similar to those of human arteries and aneurysms.…”
Section: Introductionmentioning
confidence: 99%